Theory and Modern Applications

# Some identities of higher order Barnes-type q-Bernoulli polynomials and higher order Barnes-type q-Euler polynomials

## Abstract

In this paper, we consider higher order Barnes-type q-Bernoulli polynomials and numbers and investigate some identities of them. Furthermore, we discuss some identities of higher order Barnes-type q-Euler polynomials and numbers.

## Introduction

Let p be a given odd prime number. Throughout this paper, we assume that $$\mathbb{Z}_{p}$$, $$\mathbb{Q}_{p}$$ and $$\mathbb{C}_{p}$$ will, respectively, denote the rings of p-adic integers, the fields of p-adic numbers and the completion of algebraic closure of $$\mathbb{Q}-p$$. The p-adic norm $$|p|_{p}=\frac{1}{p}$$. Let $$\operatorname{UD}(\mathbb{Z}_{p})$$ be the space of uniformly differentiable functions on $$\mathbb{Z}_{p}$$. For $$f\in \operatorname{UD}(\mathbb{Z}_{p})$$, the bosonic p-adic integral on $$\mathbb {Z}_{p}$$ is defined as

$$I_{0}(f)= \int_{\mathbb{Z}_{p}} f(x)\, d \mu_{0}(x) =\lim_{N\rightarrow\infty} \frac{1}{p^{N}} \sum _{x=0}^{p^{N}-1} f(x) \quad (\mbox{see [1--12]}).$$
(1)

It is well known that an integral equation of the bosonic p-adic integral $$I_{0}$$ on $$\mathbb{Z}_{p}$$,

$$I_{0}(f_{1})-I_{0}(f)=f'(0),$$
(2)

where $$f_{1}(x)=f(x+1)$$. Higher order Bernoulli polynomials are defined by Kim to be

$$\biggl( \frac{t}{e^{t}-1} \biggr)^{r} e^{xt} = \sum_{n=0}^{\infty}B_{n}^{(r)} (x) \frac{t^{n}}{n!}\quad (\mbox{see [5, 13--16]}).$$
(3)

When $$x=0$$, $$B_{n}^{(r)}=B_{n}^{(r)}(0)$$ is called higher order Bernoulli numbers. Higher order Barnes-type Bernoulli polynomials are defined by Kim to be

$$\prod_{i=1}^{r} \biggl( \frac{t}{e^{a_{i}t}-1} \biggr)^{r} e^{xt} = \sum _{n=0}^{\infty}B_{n}^{(r)} (x|a_{1}, \ldots, a_{r}) \frac{t^{n}}{n!}\quad (\mbox{see [11--15, 17--21]}).$$
(4)

When $$x=0$$, $$B_{n}^{(r)}(a_{1}, \ldots, a_{r})=B_{n}^{(r)}(0|a_{1}, \ldots, a_{r})$$ is called higher order Barnes-type Bernoulli numbers.

In this paper we consider higher order Barnes-type q-Bernoulli polynomials and numbers and investigate some identities of them. We also discuss some identities of higher order Barnes-type q-Euler polynomials and numbers.

## Higher order Barnes-type q-Bernoulli polynomials and numbers

In this section, we assume that $$q\in\mathbb{C}_{p}$$ with $$|1-q|_{p}< p^{-\frac{1}{p-1}}$$. By (2), if we take $$f(x)=q^{y} e^{(x+y)t}$$, then we get

$$\int_{\mathbb{Z}_{p}} q^{y} e^{(x+y)t} \, d \mu_{0} (y)= \frac{t+ \log q}{qe^{t}-1}e^{xt},$$
(5)

where $$f_{1}(x)=f(x+1)$$. q-Bernoulli polynomials are defined by Kim to be

$$\frac{t+ \log q}{qe^{t}-1}e^{xt} = \sum _{n=0}^{\infty}B_{n,q}(x) \frac {t^{n}}{n!}\quad (\mbox{see [13--15, 17, 19--21]}).$$
(6)

When $$x=0$$, $$B_{n,q}=B_{n,q}(0)$$ is called q-Bernoulli numbers.

Higher order q-Bernoulli polynomials are defined as

$$\biggl( \frac{t+ \log q}{qe^{t}-1} \biggr)^{r} e^{xt} = \sum_{n=0}^{\infty}B_{n,q}^{(r)}(x) \frac{t^{n}}{n!}.$$
(7)

When $$x=0$$, $$B_{n,q}^{(r)}=B_{n,q}^{(r)}(0)$$ is called higher order q-Bernoulli numbers.

We define higher order Barnes-type q-Bernoulli polynomials as follows:

$$\frac{(t+ \log q)^{r}}{ ( q^{a_{1}}e^{a_{1}t}-1 )\cdots ( q^{a_{r}}e^{a_{r}t}-1 )} e^{xt} = \sum _{n=0}^{\infty}B_{n,q}(x|a_{1}, \ldots, a_{r}) \frac{t^{n}}{n!}.$$
(8)

When $$x=0$$, $$B_{n,q}(a_{1}, \ldots, a_{r})= B_{n,q}(0|a_{1}, \ldots, a_{r})$$ is called higher order Barnes-type q-Bernoulli numbers. By (5), we get

\begin{aligned}& \int_{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}t_{r}} e^{(a_{1}x_{1}+\cdots +a_{r}x_{r} +x)t} \, d\mu_{0}(x_{1})\cdots \, d\mu_{0} (x_{r}) \\& \quad = \Biggl( \prod_{i=1}^{r} a_{i} \Biggr) \frac{(t+ \log q)^{r}}{ ( q^{a_{1}}e^{a_{1}t}-1 )\cdots ( q^{a_{r}}e^{a_{r}t}-1 )} e^{xt}. \end{aligned}
(9)

By (9) and (8), we get

\begin{aligned}& \sum_{n=0}^{\infty}B_{n,q}(x|a_{1}, \ldots, a_{r}) \frac{t^{n}}{n!} \\& \quad =\frac{(t+ \log q)^{r}}{ ( q^{a_{1}}e^{a_{1}t}-1 )\cdots ( q^{a_{r}}e^{a_{r}t}-1 )} e^{xt} \\& \quad = \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}} \cdots\int _{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots +a_{r}x_{r}}e^{(a_{1}x_{1}+\cdots+a_{r}x_{r}+x)t} \, d \mu_{0}(x_{1})\cdots\, d\mu_{0}(x_{r}) \\& \quad = \sum_{n=0}^{\infty}\Biggl( \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}} \cdots\int _{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}+x} \\& \qquad {}\times(a_{1}x_{1}+ \cdots+a_{r}x_{r}+x)^{n} \, d\mu_{0}(x_{1}) \cdots\, d\mu_{0}(x_{r}) \Biggr) \frac{t^{n}}{n!}. \end{aligned}
(10)

From (10), we obtain the following theorem.

### Theorem 2.1

Let $$n\in\mathbb{N}\cup\{0\}$$. Then we have

\begin{aligned}& B_{n,q}(x| a_{1}, \ldots, a_{r}) \\& \quad = \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}} \cdots\int _{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}+x} \\& \qquad {}\times(a_{1}x_{1}+ \cdots+a_{r}x_{r}+x)^{n} \, d\mu_{0}(x_{1}) \cdots\, d\mu_{0}(x_{r}). \end{aligned}
(11)

From (1), we have

\begin{aligned} \int_{\mathbb{Z}_{p}} f(x)\, d \mu_{0}(x) =& \lim_{N\rightarrow\infty} \frac{1}{p^{N}} \sum_{x=0}^{dp^{N}-1} f(x) \\ =& \frac{1}{d} \lim_{N\rightarrow\infty} \frac{1}{p^{N}} \sum _{a=0}^{d-1} \sum _{x=0}^{p^{N}-1} f(a+dx) \\ =& \frac{1}{d}\sum_{a=0}^{d-1} \int _{\mathbb{Z}_{p}} f(a+dx)\, d \mu_{0}(x). \end{aligned}
(12)

By (12), we have

\begin{aligned}& \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1}\int_{\mathbb{Z}_{p}} \cdots\int _{\mathbb{Z}_{p}} q^{a_{1} x_{1}+\cdots+a_{r} x_{r}} e^{(a_{1}d x_{1}+\cdots+a_{r}d x_{r}+x)t} \, d \mu_{0}(x_{1})\cdots\, d\mu_{0}(x_{r}) \\& \quad = \frac{1}{d^{r}}\sum_{l_{1}, \ldots, l_{r}=0}^{d-1} q^{a_{1}l_{1}\cdots+a_{r}l_{r}} \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}}\cdots\int _{\mathbb{Z}_{p}} q^{a_{1}\, dx_{1}+\cdots+a_{r}\, dx_{r}} \\& \qquad {}\times e^{(a_{1}l_{1}\cdots+a_{r}l_{r}+ x+ a_{1}\, dx_{1}+\cdots+a_{r}\, dx_{r})t} \, d \mu_{0}(x_{1})\cdots\, d\mu_{0}(x_{r}) \\& \quad = \frac{1}{d^{r}}\sum_{l_{1}, \ldots, l_{r}=0}^{d-1} q^{a_{1}l_{1}\cdots+a_{r}l_{r}} \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1}\int_{\mathbb{Z}_{p}}\cdots\int _{\mathbb{Z}_{p}} q^{a_{1}\, dx_{1}+\cdots+a_{r}\, dx_{r}} \\& \qquad {}\times e^{ ( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r} +x}{d} + a_{1}x_{1}+\cdots+a_{r} x_{r} ) \, dt}\, d \mu_{0}(x_{1})\cdots\, d\mu_{0}(x_{r}) \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{d-1}q^{a_{1}l_{1}\cdots+a_{r}l_{r}} \sum_{n=0}^{\infty}\frac{d^{n}}{d^{r}} \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}}\cdots\int _{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} \\& \qquad {}\times \biggl( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r} +x}{d} + a_{1}x_{1}+ \cdots+a_{r} x_{r} \biggr)^{n} \, d \mu_{0}(x_{1})\cdots\, d\mu_{0}(x_{r}) \frac{t^{n}}{n!} \\& \quad = \sum_{n=0}^{\infty}d^{n-r} \sum_{l_{1}, \ldots, l_{r}=0}^{d-1} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} B_{n,q} \biggl( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r} +x}{d} \Big| a_{1}, \ldots, a_{r} \biggr) \frac{t^{n}}{n!}. \end{aligned}
(13)

By (8), (9), (11) and (13), we obtain the following theorem.

### Theorem 2.2

Let $$n\in\mathbb{N}\cup\{0\}$$. Then we have

\begin{aligned}& B_{n,q}(x| a_{1}, \ldots, a_{r}) \\& \quad = d^{n-r} \sum_{l_{1}, \ldots, l_{r}=0}^{d-1}q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} B_{n,q} \biggl( \frac{l_{1}x_{1}+\cdots+l_{r}x_{r} +x}{d} \Big| a_{1}, \ldots, a_{r} \biggr). \end{aligned}
(14)

It is well known that an integral equation of the bosonic p-adic integral $$I_{0}$$ on $$\mathbb{Z}_{p}$$ satisfies the following integral equation:

$$I_{0}(f_{n})-I_{0}(f)= \sum _{i=1}^{n-1} f'(i).$$
(15)

If we take $$f(x_{i})=q^{a_{i}x_{i}}e^{a_{i}x_{i}t}$$ for $$i=1, \ldots, r$$, then we have

$$\int_{\mathbb{Z}_{p}} q^{a_{i} x_{i}} e^{a_{i}x_{i} t}\, d\mu_{0}(x_{i}) =\frac{a_{i}(t+\log q)}{q^{a_{i}n}e^{a_{i} nt}-1}\sum _{l=0}^{n-1} q^{a_{i} l}e^{a_{i}lt}.$$
(16)

By (16), we get

\begin{aligned}& \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}} \cdots \int _{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} e^{(a_{1}x_{1}+\cdots+a_{r}x_{r}) t}\, d \mu_{0}(x_{1}) \cdots \, d\mu_{0}(x_{r}) \\& \quad = \frac{(t+\log q)^{r}}{ (q^{a_{1}n}e^{a_{1} nt}-1 ) \cdots (q^{a_{r}n}e^{a_{r} nt}-1 )} \sum_{l_{1}, \ldots, l_{r}=0}^{n-1} q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} e^{(a_{1}l_{1}+\cdots+a_{r}l_{r}) t} \\& \quad = \Biggl( \sum_{k=0}^{\infty}B_{k,q}(na_{1}, \ldots, na_{r}) \frac {t^{k}}{k!} \Biggr)\sum_{l_{1}, \ldots, l_{r}=0}^{n-1} q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} \sum _{j=0}^{\infty}(a_{1}l_{1}+ \cdots+ a_{r}l_{r})^{j} \frac{t^{j}}{j!} \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{n-1} \sum _{k=0}^{\infty}\sum_{j=0}^{\infty}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} (a_{1}l_{1}+\cdots+ a_{r}l_{r})^{j} B_{k,q}(na_{1}, \ldots, na_{r})\frac{t^{k+j}}{k!j!} \\& \quad = \sum_{m=0}^{\infty}\sum _{l_{1}, \ldots, l_{r}=0}^{n-1} \sum_{j=0}^{m} \binom{m}{j} q^{a_{1}l_{1}+\cdots+a_{r}l_{r}}(a_{1}l_{1}+\cdots+ a_{r}l_{r})^{j} \\& \qquad {}\times B_{m-j,q}(na_{1}, \ldots, na_{r}) \frac{t^{m}}{m!}. \end{aligned}
(17)

Thus, by (11) and (17), we obtain the following theorem.

### Theorem 2.3

Let $$n\in\mathbb{N}\cup\{0\}$$. Then we have

\begin{aligned}& B_{n,q}( a_{1}, \ldots, a_{r}) \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{n-1} \sum _{j=0}^{m} \binom{m}{j} q^{a_{1}l_{1}+\cdots+a_{r}l_{r}}(a_{1}l_{1}+ \cdots+ a_{r}l_{r})^{j} B_{m-j,q}(na_{1}, \ldots, na_{r}). \end{aligned}
(18)

By (16), we get

\begin{aligned}& \Biggl( \prod_{i=1}^{r} a_{i} \Biggr)^{-1} \int_{\mathbb{Z}_{p}} \cdots \int _{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} e^{(a_{1}x_{1}+\cdots+a_{r}x_{r}) t}\, d \mu_{0}(x_{1}) \cdots \, d\mu_{0}(x_{r}) \\& \quad = \frac{(t+\log q)^{r}}{ (q^{a_{1}n}e^{a_{1} nt}-1 ) \cdots (q^{a_{r}n}e^{a_{r} nt}-1 )} \sum_{l_{1}, \ldots, l_{r}=0}^{n-1} q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} e^{(a_{1}l_{1}+\cdots+a_{r}l_{r}) t} \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{n-1}\frac{(t+\log q)^{r}}{ (q^{a_{1}n}e^{a_{1} nt}-1 ) \cdots (q^{a_{r}n}e^{a_{r} nt}-1 )} q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} e^{(a_{1}l_{1}+\cdots+a_{r}l_{r}) t} \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{n-1}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} \frac{(t+\log q)^{r}}{ (q^{a_{1}n}e^{a_{1} nt}-1 ) \cdots (q^{a_{r}n}e^{a_{r} nt}-1 )} e^{\frac{a_{1}l_{1}+\cdots+a_{r}l_{r}}{n} nt} \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{n-1}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} \sum_{m=0}^{\infty}B_{m,q^{n}} \biggl( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r}}{n}\Big| a_{1},\ldots, a_{r} \biggr) \frac{n^{m}t^{m}}{m!} \\& \quad = \sum_{m=0}^{\infty}n^{m} \sum_{l_{1}, \ldots, l_{r}=0}^{n-1}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} B_{m,q^{n}} \biggl( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r}}{n}\Big| a_{1},\ldots, a_{r} \biggr) \frac{t^{m}}{m!}. \end{aligned}
(19)

Thus, by (11) and (19), we obtain the following theorem.

### Theorem 2.4

Let $$n\in\mathbb{N}\cup\{0\}$$. Then we have

$$B_{m,q}( a_{1}, \ldots, a_{r}) = n^{m} \sum_{l_{1}, \ldots, l_{r}=0}^{n-1}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} B_{m,q^{n}} \biggl( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r}}{n}\Big| a_{1},\ldots, a_{r} \biggr) .$$
(20)

## Higher order Barnes-type q-Euler polynomials

Higher Euler polynomials are defined as

$$\biggl( \frac{2}{e^{t}+1} \biggr)^{r} e^{xt} =\sum_{n=0}^{\infty}E_{n} (x) \frac{t^{n}}{n!} \quad (\mbox{see [17--19, 22--24]}).$$
(21)

When $$x=0$$, $$E_{n} =E_{n} (0)$$ is called higher Euler numbers. For $$f\in \operatorname{UD}(\mathbb{Z}_{p})$$, the fermionic p-adic integral on $$\mathbb {Z}_{p}$$ is defined by Kim to be

$$I_{-1}(f)= \int_{\mathbb{Z}_{p}} f(x) \, d \mu_{-1}(x) =\lim_{N\rightarrow\infty} \sum _{x=0}^{p^{N}-1} f(x) (-1)^{x} \quad (\mbox{see }).$$
(22)

It is well known that an integral equation of the fermionic p-adic integral on $$\mathbb{Z}_{p}$$ is

$$I_{-1}(f_{1})+I_{-1}(f)=2f(0),$$
(23)

where $$f_{1}(x)=f(x+1)$$.

Let $$a_{1}, \ldots, a_{r}\in\mathbb{C}_{p}\setminus\{0\}$$. Higher order Barnes-type Euler polynomials are defined as

$$\frac{2^{r}}{ (e^{a_{1}t}+1 )\cdots (e^{a_{r}t}+1 )} e^{xt} = \sum _{n=0}^{\infty}E_{n} (x|a_{1}, \ldots, a_{r}) \frac{t^{n}}{n!}\quad (\mbox{see [18, 19, 23]}).$$
(24)

When $$x=0$$, $$E_{n}(a_{1}, \ldots, a_{r})=E_{n}(0|a_{1}, \ldots, a_{r})$$ is called higher order Barnes-type Euler numbers. We define higher order Barnes-type q-Euler polynomials as follows:

$$\frac{2^{r}}{ ( q^{a_{1}}e^{a_{1}t}+1 )\cdots ( q^{a_{r}}e^{a_{r}t}+1 )} e^{xt} = \sum _{n=0}^{\infty}E_{n,q}(x|a_{1}, \ldots, a_{r}) \frac{t^{n}}{n!}.$$
(25)

When $$x=0$$, $$E_{n,q}(a_{1}, \ldots, a_{r})= E_{n,q}(0|a_{1}, \ldots, a_{r})$$ is called higher order Barnes-type q-Euler numbers.

By (23), if we take $$f(x_{i})=q^{a_{i}x_{i}} e^{a_{i}x_{i}t}$$ for $$i=1,\ldots,r$$, then we have

$$\int_{\mathbb{Z}_{p}} q^{a_{i}x_{i}} e^{a_{i}x_{i}t}\, d\mu_{-1}(x_{i})= \frac{2}{q^{a_{i}x_{i}}e^{a_{i}x_{i} t}+1}.$$
(26)

By (26), we get

\begin{aligned}& \int_{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}t_{r}} e^{(a_{1}x_{1}+\cdots +a_{r}x_{r} +x)t} \, d\mu_{0}(x_{1})\cdots\, d\mu_{0} (x_{r}) \\& \quad = \frac{2^{r}}{ ( q^{a_{1}}e^{a_{1}t}+1 )\cdots ( q^{a_{r}}e^{a_{r}t}+1 )} e^{xt}. \end{aligned}
(27)

By (24) and (27), we get

\begin{aligned}& \sum_{n=0}^{\infty}E_{n,q}(x|a_{1}, \ldots, a_{r})\frac{t^{n}}{n!} \\& \quad = \frac{2^{r}}{ ( q^{a_{1}}e^{a_{1}t}+1 )\cdots ( q^{a_{r}}e^{a_{r}t}+1 )} e^{xt} \\& \quad = \int_{\mathbb{Z}_{p}} \cdots\int_{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots +a_{r}x_{r}}e^{(a_{1}x_{1}+\cdots+a_{r}x_{r}+x)t} \, d\mu_{-1}(x_{1})\cdots\, d\mu_{-1}(x_{r}) \\& \quad = \sum_{n=0}^{\infty}\int _{\mathbb{Z}_{p}} \cdots\int_{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} (a_{1}x_{1}+\cdots+a_{r}x_{r}+x)^{n} \, d\mu_{-1}(x_{1})\cdots\, d\mu_{-1}(x_{r}) \frac{t^{n}}{n!}. \end{aligned}
(28)

From (28), we obtain the following theorem.

### Theorem 3.1

Let $$n\in\mathbb{N}\cup\{0\}$$. Then we have

\begin{aligned}& E_{n,q}(x| a_{1}, \ldots, a_{r}) \\& \quad = \int_{\mathbb{Z}_{p}} \cdots\int_{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} (a_{1}x_{1}+\cdots+a_{r}x_{r}+x)^{n} \, d\mu_{-1}(x_{1})\cdots\, d\mu_{-1}(x_{r}). \end{aligned}
(29)

From (22), we have

\begin{aligned} \begin{aligned}[b] \int_{\mathbb{Z}_{p}} f(x) \, d \mu_{-1}(x) &= \lim_{N\rightarrow\infty} \sum_{x=0}^{dp^{N}-1} f(x) (-1)^{x} \\ &= \frac{1}{d} \lim_{N\rightarrow\infty} \sum _{a=0}^{d-1} \sum_{x=0}^{p^{N}-1} (-1)^{a+x}f(a+dx) \\ &= \frac{1}{d}\sum_{a=0}^{d-1}(-1)^{a} \int_{\mathbb{Z}_{p}} f(a+dx)\, d \mu_{-1}(x). \end{aligned} \end{aligned}
(30)

By (30), if we take $$f(x_{i})=q^{a_{i}x_{i}}e^{a_{i}x_{i}t}$$ for $$i=1, \ldots, r$$, then we have

\begin{aligned} \int_{\mathbb{Z}_{p}} q^{a_{i}x_{i}}e^{a_{i}x_{i}t}\, d \mu_{-1}(x) =& \sum_{a=0}^{d-1}(-1)^{a} \int_{\mathbb{Z}_{p}} q^{a_{i}(a+dx-i)}e^{a_{i}(a+dx_{i})t} \, d \mu_{-1}(x_{i}) \\ =& \sum_{a=0}^{d-1}(-1)^{a} q^{a_{i} a}e^{a_{i} a t} \int_{\mathbb{Z}_{p}} q^{a_{i} dx_{i}}e^{a_{i} dx_{i}t}\, d \mu_{-1}(x_{i}). \end{aligned}
(31)

By (31), we get

\begin{aligned}& \int_{\mathbb{Z}_{p}} \cdots\int_{\mathbb{Z}_{p}} q^{a_{1}x_{1}+\cdots+a_{r}x_{r}} e^{(a_{1}x_{1}+\cdots+a_{r}x_{r}+x)t} \, d\mu_{-1}(x_{1})\cdots \, d\mu_{-1}(x_{r}) \\& \quad = \sum_{l_{1}, \ldots, l_{r}=0}^{d-1}(-1)^{l_{1}+\cdots +l_{r}}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} \\& \qquad {}\times\int_{\mathbb{Z}_{p}}\cdots\int_{\mathbb{Z}_{p}} q^{a_{1}\, dx_{1}+\cdots+a_{r}\, dx_{r}} e^{ (\frac{a_{1}l_{1}+\cdots+a_{1}l_{r} + x}{d}+ a_{1}x_{1}+\cdots+a_{r} x_{r} )\, dt} \, d\mu_{-1}(x_{1})\cdots \, d\mu_{-1}(x_{r}) \\& \quad = \sum_{n=0}^{\infty}d^{n} \sum_{l_{1}, \ldots, l_{r}=0}^{d-1}(-1)^{l_{1}+\cdots+l_{r}}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} \int_{\mathbb {Z}_{p}}\cdots\int_{\mathbb{Z}_{p}} q^{a_{1}\, dx_{1}+\cdots+a_{r}\, dx_{r}} \\& \qquad {}\times \biggl(\frac{a_{1}l_{1}+\cdots+a_{1}l_{r} + x}{d}+ a_{1}x_{1}+ \cdots+a_{r} x_{r} \biggr)^{n} \, d \mu_{-1}(x_{1})\cdots\, d\mu_{-1}(x_{r}) \frac{t^{n}}{n!} \\& \quad = \sum_{n=0}^{\infty}d^{n} \sum_{l_{1}, \ldots, l_{r}=0}^{d-1}(-1)^{l_{1}+\cdots+l_{r}}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} \\& \qquad {}\times E_{n,q^{d}} \biggl( \frac{a_{1}l_{1}+\cdots+a_{r}l_{r} + x}{d} \Big| a_{1}, \ldots, a_{r} \biggr) \frac{t^{n}}{n!}. \end{aligned}
(32)

By (27) and (32), we obtain the following theorem.

### Theorem 3.2

Let $$n\in\mathbb{N}\cup\{0\}$$. Then we have

\begin{aligned}& E_{n,q}(x| a_{1}, \ldots, a_{r}) \\& \quad = d^{n} \sum_{l_{1}, \ldots, l_{r}=0}^{d-1}(-1)^{l_{1}+\cdots +l_{r}}q^{a_{1}l_{1}+\cdots+a_{r}l_{r}} E_{n,q^{d}} \biggl( \frac{a_{1}l_{1}+\cdots +a_{r}l_{r} + x}{d} \Big| a_{1}, \ldots, a_{r} \biggr). \end{aligned}

## References

1. Kim, T: Barnes’ type multiple degenerate Bernoulli and Euler polynomials. Appl. Math. Comput. 258, 556-564 (2015)

2. Kim, T, Kim, DS, Bayad, A, Rim, S-H: Identities on the Bernoulli and the Euler numbers and polynomials. Ars Comb. 107, 455-463 (2012)

3. Kim, T, Dolgy, DV, Kim, DS, Rim, S-H: A note on the identities of special polynomials. Ars Comb. 113A, 97-106 (2014)

4. Kim, T: On the analogs of Euler numbers and polynomials associated with p-adic q-integral on $$\mathbb{Z}_{p}$$ at $$q=-1$$. J. Math. Anal. Appl. 331(2), 779-792 (2007)

5. Kim, DS, Kim, T: A note on poly-Bernoulli and higher-order poly-Bernoulli polynomials. Russ. J. Math. Phys. 22(1), 26-33 (2015)

6. Lim, D, Do, Y: Some identities of Barnes-type special polynomials. Adv. Differ. Equ. 2015, 42 (2015)

7. Luo, Q-M, Qi, F: Relationships between generalized Bernoulli numbers and polynomials and generalized Euler numbers and polynomials. Adv. Stud. Contemp. Math. 7(1), 11-18 (2003)

8. Ozden, H: p-Adic distribution of the unification of the Bernoulli, Euler and Genocchi polynomials. Appl. Math. Comput. 218(3), 970-973 (2011)

9. Park, J-W, Rim, S-H: On the modified q-Bernoulli polynomials with weight. Proc. Jangjeon Math. Soc. 17(2), 231-236 (2014)

10. Ryoo, CS, Kwon, HI, Yoon, J, Jang, YS: Fourier series of the periodic Bernoulli and Euler functions. Abstr. Appl. Anal. 2014, Article ID 856491 (2014)

11. Ding, D, Yang, J: Some identities related to the Apostol-Euler and Apostol-Bernoulli polynomials. Proc. Jangjeon Math. Soc. 17(1), 115-123 (2014)

12. Jang, LC: A family of Barnes-type multiple twisted q-Euler numbers and polynomials related to fermionic p-adic invariant integrals on $$\mathbb{ Z}_{p}$$. J. Comput. Anal. Appl. 13(2), 376-387 (2011)

13. Andrews, GE, Askey, R, Roy, R: Special Functions. Encyclopedia of Mathematics and Its Applications, vol. 71. Cambridge University Press, Cambridge (1999). ISBN:0-521-62321-9; 0-521-78988-5

14. Bayad, A, Kim, T: Results on values of Barnes polynomials. Rocky Mt. J. Math. 43(6), 1857-1869 (2013)

15. Bayad, A, Kim, T, Kim, W, Lee, SH: Arithmetic properties of q-Barnes polynomials. J. Comput. Anal. Appl. 15(1), 111-117 (2013)

16. Kang, D, Jeong, J-J, Lee, BJ, Rim, S-H, Choi, SH: Some identities of higher order Genocchi polynomials arising from higher order Genocchi basis. J. Comput. Anal. Appl. 17(1), 141-146 (2014)

17. Chen, C-P, Srivastava, HM: Some inequalities and monotonicity properties associated with the gamma and psi functions and the Barnes G-function. Integral Transforms Spec. Funct. 22(1), 1-15 (2011)

18. Kim, T: p-Adic q-integrals associated with the Changhee-Barnes’ q-Bernoulli polynomials. Integral Transforms Spec. Funct. 15(5), 415-420 (2004)

19. Kim, T: Barnes-type multiple q-zeta functions and q-Euler polynomials. J. Phys. A 43(25), 255201 (2010)

20. Kim, T: On the multiple q-Genocchi and Euler numbers. Russ. J. Math. Phys. 15(4), 482-486 (2008)

21. Kim, T, Rim, S-H: On Changhee-Barnes’ q-Euler numbers and polynomials. Adv. Stud. Contemp. Math. 9(2), 81-86 (2004)

22. Can, M, Cenkci, M, Kurt, V, Simsek, Y: Twisted Dedekind type sums associated with Barnes’ type multiple Frobenius-Euler l-functions. Adv. Stud. Contemp. Math. 18(2), 135-160 (2009)

23. Jang, L, Kim, T, Kim, Y-H, Hwang, K-W: Note on the q-extension of Barnes’ type multiple Euler polynomials. J. Inequal. Appl. 2009, Article ID 13532 (2009)

24. Kim, T: On Euler-Barnes multiple zeta functions. Russ. J. Math. Phys. 10(3), 261-267 (2003)

## Author information

Authors

### Corresponding author

Correspondence to Lee-Chae Jang.

### Competing interests

The authors declare that they have no competing interests.

### Authors’ contributions

All authors contributed equally to this work. All authors read and approved the final manuscript.

## Rights and permissions 